Informative Cooperative Path Planning and Time-Varying Formation Control of Heterogeneous Mobile Robots - Xiaojuan Ma; Liangshun Wang; Xiaomei Liu (IEEE Access)
This paper simultaneously addresses the problems of informative cooperative path planning and time-varying formation control for heterogenous multi-robot systems with distance constraints and disturbances to achieve efficient data collection. A protocol for time-varying formation control is proposed to achieve the desired formation, accounting for robot dynamics and disturbances under fixed and random switching topology. The robot in the team is constrained by the distance to its neighbors, and rigid graph theory is applied for formation control. In addition, a path planning strategy with formation constraints is investigated using the constructed field with sampled data. The configuration of path planning and formation control is shown, and the field gradient climbing algorithm is developed accordingly. Two cases of simulation results substantiate the effectiveness of the developed path planning and formation control algorithm.